ANALISIS DETERMINAN KEJADIAN STROKE BERULANG - Mu'awanah Mu'awanah; Agus Prasetyo; Resmi Pangaribuan; M Zainal Abidin (Ensiklopedia of Journal, 2026)
Stroke is a noncommunicable disease that is a leading cause of long-term disability and death in many countries, including Indonesia. Stroke remains one of the leading causes of death and disability worldwide, with the number of cases continuing to rise each year. The objective of this study was to analyze the determinants of recurrent stroke. The objective of this study was to analyze the determinants of recurrent stroke. A cross-sectional study design was used in this research. The study was conducted at a hospital in West Sumatra Province. The sample consisted of 60 respondents. Purposive sampling was used. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed an association between dietary patterns (p-value: 0.000) and physical activity (p-value: 0.036) and the occurrence of recurrent stroke. It is recommended that hospital management and healthcare workers improve the quality of care by enhancing stroke patients’ knowledge of the risk of recurrent stroke through proper discharge planning by healthcare workers. This will increase patients’ knowledge, leading to behavioral changes in physical activity and healthy dietary habits to prevent recurrent strokes.Keywords: Physical Activity, Diet, Stroke